PRINCIPLES OF JUSTICE IN THE AFFIRMATIVE ACTIONS FOR ACCESS TO BRAZILIAN HIGHER EDUCATION - Rosa, Chaiane de Medeiros (2017)
This study aims to investigate how the principles of justice focus on affirmative politics for access to Brazilian higher education. This research comes from the understanding that there are insufficient vacancies in higher education institutions in the country, considering that only 16.4% of individuals with regular aged between 18 and 24 years are enrolled in this level of education, according to the data of Census of Higher Education of 2013. For those from social classes historically excluded from society, such as egresses of public schools, blacks, Indians, maroons, disabled persons, among other groups, the exclusion of that level of education appears to be even more perverse. This context, therefore, requires state intervention, which, from the perspective of justice, is the distributor of resources agent. In these terms, from the socio-economic and educational profile of racial ethnic minorities in the country, especially black and brown, presents a theoretical study that marks the relevance of affirmative action politics for access to higher education, which is in line with principles of justice distributive, and thus, of social justice.